Restaurant Marketing Efforts on Instagram: Influence on Consumer Behavior - Rayhan Gunaningrat; Istiyawati Rahayu; Erna Chotidjah Suhatmi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study investigates the relationship between Instagram marketing efforts and willingness to pay a premium price as mediated by trust and brand image in order to validate the theory with practical application, particularly in the restaurant industry. To test the proposed hypothesis, this study employs a quantitative approach with a causal research design. Data was gathered through a survey of 100 respondents via an online questionnaire, which was distributed to social media users in Indonesia who had visited a restaurant that was actively marketing on social media. In addition, a structural equation model was developed to analyze these research data. This study evaluates the company's Instagram marketing efforts as a whole, combining six factors (entertainment, interaction, trendiness, customization, electronic word of mouth, and risk). The results of this study reveal that marketing efforts through Instagram directly encourage consumers to pay premium prices and influence consumer brand preferences. Out of the six indicators, entertainment and perceived risk have the greatest influence on consumer brand preference and consumer willingness to pay a premium price.